Liming and compost amendment of heavy metal contaminated soil reduced pb accumulation in Ocimum Gratissimum L, enhanced secondary metabolism and chlorophyll formation (2022)
Soil contamination by heavy metals limits plant metabolic processes and development. Technique that immobilizes metal in the soil and reduced uptake by crop is preferred. Effects of liming and compost amendment on Pb immobilization and secondary metabolism of Osmium gratissimum L. planted on lead-acid battery wastes contaminated soil were studied. Four levels of lime (0 ton/ha, 2 ton/ha, 4 ton/ha and 8 ton/ha) and compost (0 ton/ha, 10 ton/ha, 20 ton/ha and 30 ton/ha) were used while uncontaminated and contaminated soil without amendments served as checks. Data were collected on growth and yield parameters, nutrient uptake, leaf chlorophyll and secondary metabolites (Total phenols, Terpenoids and Flavonoids) contents. Addition of compost (30 t/ha) and in combination with lime (2 t/ha) reduced post-cropping soil Pb concentration and accumulation in plant. Biomass accumulation was reduced in Ocimum gratissimum grown on contaminated soil by 85.23% compared to uncontaminated control. Liming and compost addition however enhanced the growth and yield of Occimum spp on contaminated soil and there was increase in the phenolic and terpenoids production by 78.53% in the plant grown on contaminated soil compared to uncontaminated control. Sole application of lime however inhibited phenolic production except in combination with compost whereas flavonoid production was enhanced by liming. Similarly,there was 56.21% increase in chlorophyll content of Occimum spp grown on contaminated soil amended with 30 t/ha compost in combination with lime at 8 t/ha. Highest rate of compost (30 t/ha) in combination with 2 t/ha lime was more effective in improving the chlorophyll content, growth and yield of Ocimum gratissimum on Pb contaminated soil